The impact of school policy and stakeholders' actions on student learning: A longitudinal study. (April 2015) - Kyriakides, Leonidas; Creemers, Bert P.M.; Antoniou, Panayiotis; Demetriou, Demetris; Charalambous, Charalambos Y.
Abstract: This paper proposes a theoretical framework on how school policy can promote student learning. School policy is considered to have an indirect effect on student achievement by changing school stakeholders' actions toward improving the School Learning Environment (SLE) and teaching practice. A reciprocal relationship between school policy and stakeholders' actions is also considered. A longitudinal study was conducted to test the framework's main assumptions. A stratified sample of 64 primary schools was selected and students' achievement in Mathematics at the beginning of Grade 4 and at the end of the next three consecutive school years was measured, alongside the school policy and teachers' actions with regards to issues associated with teaching and the SLE. The results of multilevel structural equation modelling analyses supported the main assumptions of the framework. Implications for the development of school policy are drawn and suggestions for further research are provided. Highlights: A theoretical framework on how school policy promotes student learning is proposed. A longitudinal study provided empirical validity to the framework. School policy has an effect on learning through changing stakeholders' actions. A reciprocal relationship between school policy and stakeholders' actions is found. Cross-sectional studies undervalue the impact of school policy on student learning.